Investigating successes and failures of implementing green infrastructure as a way to enhance sustainability: the case of Tbilisi, Georgia - Tavdgiridze, Ann (My University, 2021)
This study conducted an analysis of the Green Infrastructure Policy in Tbilisi, Georgia with the aim of determining its failures and successes. Green infrastructure is the interconnection of elements such as green areas, and natural features of the surroundings. Through the scrutiny of various documents such as the Green City Action Plan and other secondary sources, the study was able to determine the successes and failure of implementing green infrastructure in Tbilisi, Georgia. The sources showed that the city has not improved its infrastructure, which has further delayed its sustainability goals. Besides, the realization of the Green Infrastructure Policy in Tbilisi faces other problems such as lack of community participation. The researcher used case study analysis to develop the findings. Further, the study sought to determine whether implementation of green infrastructure has any effect on air pollution. The study found out that there exist both successes and weaknesses of the Green Infrastructure Project in Tbilisi
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, as a partial fulfilment of the requirements for the degree of Masters of Urban Studies in the Field of Urban Management, 2021